Development and Validation of Data-Driven Decision Making in Schools Scale - Barzan Batuk; Hasan Basri Memduhoğlu (Van Yüzüncü Yıl Üniversitesi Eğitim Fakültesi Dergisi)
Data has become an essential part of educational decisions about teaching and learning, classroom-level issues, management or a range of other decisions faced by educators. Due to the widespread use of data, which is a resource used and benefited from in making qualified decisions, the need for a valid and reliable measurement tool to determine the perceptions of administrators and teachers towards data-driven decision making in schools has arisen. For this purpose, a five-point Likert-type scale called "Data-Driven Decision Making in Schools Scale" was developed through a systematic process. The sample of the study consisted of 584 teachers and administrators for exploratory factor analysis and 392 teachers and administrators for confirmatory factor analysis. The McDonald’s omega (ω) and Cronbach’s alpha (α) coefficients calculated for the scale were found to be in the range of .84 – .96, and the CR and AVE values were above .60 and between .52–.60, respectively, indicating sufficient reliability and convergent validity. After the validity and reliability were ensured, the final version of the Data-Driven Decision Making in Schools Scale consisted of 23 items and three dimensions. These dimensions are data collection and storage, data analysis and interpretation, and data-driven culture. The analysis's findings demonstrate that the 3DM-School is a valid and reliable measuring instrument for figuring out how administrators and teachers feel about making decisions in schools based on data.